HEDONIC PRICE APPROACH OF FLOOD EFFECT ON AGRICULTURAL LAND - Endah Saptutyningsih; Suryanto Suryanto (Universitas Islam Indonesia, 2011)
The natural disasters that took place in many parts of Indonesia in the last 10 years have caused an enormous losses, including agricultural sector. The objective of this paper is to estimate the magnitude of the influence of flood disaster on land price changes in Yogyakarta, using a hedonic price approach. The sample are is choosen from the vulnerable flood area mapped by Geographical Information Systems (GIS), from which farmers and land owner are selected as the respondents. The paper finds the evidence of a high level of flood stream coefficient, indicating that the flood significantly reduces the land price. The average of household’s marginal willingness to pay for the decrease in flood stream level is estimated to be Rp 2.175. Keywords: Agricultural land, marginal willingness to pay (MWTP), hedonic priceJEL classification numbers: Q15, Q19